Features of structural and functional remodeling of the heart in patients with chronic heart failure and senile asthenia syndrome - V. A. Safronenko; A. I. Chesnikova; A. V. Safronenko (Медицинский вестник Юга России, 2025)
Objective: to evaluate the features of the structural and functional parameters of the heart in patients with chronic heart failure (CHF) and senile asthenia syndrome (SSA). Materials and methods: the study involved 161 respondents with CHF on the background of arterial hypertension (AH) (82 women and 79 men) aged 80 to 91 years. Taking into account the presence of CSA, patients were divided into 2 groups: group 1 — patients with CHF and CSA (n = 84), group 2 — patients with CHF without CSA (n = 77). Screening and diagnosis of CSA were performed using the "Age is not a hindrance" questionnaire and a comprehensive geriatric assessment. To determine the structural and functional parameters of the heart, transthoracic echocardiography (EchoCG) and Doppler EchoCG studies were performed. Results: in patients with hypertension and CHF with the development of CSA, compared with patients with hypertension and CHF without CSA, statistically significantly higher values of indexed indicators of anterior-posterior LP size (ILP), LP volume (IOLP), left ventricular myocardial mass (LVMI) (p <0.05) were observed, as well as a higher percentage of the development of concentric LV remodeling (CRLH) and a smaller one — concentric LV hypertrophy (CRLH), which is associated with an increased risk of adverse cardiovascular events. Analysis of LV systolic function revealed significantly higher LV end systolic size index (ICSR), LV end diastolic size index (ICDR), LV end diastolic volume index (ICDO), LV end systolic volume index (ICSO), lower LV minute volume index (MO), this reflects a decrease in LV myocardial contractility. In addition, patients with CSA have a lower percentage of LV ejection fraction (EF): 44% versus 59.2% (p=0.002). Accordingly, among patients with CSA, a lower percentage of heart failure with preserved LV ejection fraction (LVEF) was detected (p = 0.028). There was a statistically significant decrease in DT, IVRT, and e' indices, as well as an increase in the E/e' ratio, which indicates a more pronounced progression of LV diastolic dysfunction in "fragile" patients with hypertension and CHF. Conclusion: in the presence of CSA, patients with hypertension and CHF aged 80 years and older showed more significant changes in the structural and functional parameters of the heart, indicating a more pronounced violation of systolic and diastolic function.